2010 7th IEEE Working Conference on Mining Software Repositories (MSR 2010) 2010
DOI: 10.1109/msr.2010.5463347
|View full text |Cite
|
Sign up to set email alerts
|

Mining subclassing directives to improve framework reuse

Abstract: Abstract-To help developers in using frameworks, good documentation is crucial. However, it is a challenge to create high quality documentation especially of hotspots in white-box frameworks. This paper presents an approach to documentation of object-oriented white-box frameworks which mines from client code four different kinds of documentation items, which we call subclassing directives. A case study on the Eclipse JFace userinterface framework shows that the approach can improve the state of API documentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…A "Subclassing" directive states a requirement that has to be satisfied when subclassing a library class; such directives are, e.g., related to how and when to extend a library class, implementing a library interface, overriding a library method, implementing an abstract library method (or a method from a library interface). This section deepens the empirical findings of our previous work [10], which introduced the concept of "subclassing directives".…”
Section: Subclassing Directivesupporting
confidence: 52%
See 2 more Smart Citations
“…A "Subclassing" directive states a requirement that has to be satisfied when subclassing a library class; such directives are, e.g., related to how and when to extend a library class, implementing a library interface, overriding a library method, implementing an abstract library method (or a method from a library interface). This section deepens the empirical findings of our previous work [10], which introduced the concept of "subclassing directives".…”
Section: Subclassing Directivesupporting
confidence: 52%
“…In other terms, pieces of an API's documentation that describe how to correctly and optimally use a library are API directives. This definition encompasses Dekel's [14] and Bruch's [10] definition of API directive, but is a bit broader to provide enough leeway to accommodate natural language subtleties. Next, we present three different directives from three different software packages to sketch the scope of API directives.…”
Section: Edition)]mentioning
confidence: 99%
See 1 more Smart Citation
“…The best way of manual verification is performing it by the actual user (e.g., developers), who are expert in the field [24], [40]. If this is not possible, then at least somebody outside the research group should perform the manual verification [14]. It is also suggested that rigorous inspection and testing is applied to the source code and scripts that implement the analysis approach since wrong output might not necessarily be due to poor heuristics, but simply due to defective implementations [44].…”
Section: Comments From 5 Papers]mentioning
confidence: 99%
“…Schäfer et al [36] exploit framework usage data to cluster elements of an API into building blocks that are typically used together. Finally, Bruch et al [37] present an automated framework documentation approach that mines sample applications for subclassing directives, short descriptions of how to subclass a framework class or override its methods.…”
Section: Supporting Framework Usagementioning
confidence: 99%